2013
DOI: 10.3109/21691401.2013.794354
|View full text |Cite
|
Sign up to set email alerts
|

Cell-matrix Interactions of Factor IX (FIX)-engineered human mesenchymal stromal cells encapsulated in RGD-alginate vs. Fibrinogen-alginate microcapsules

Abstract: The success of cell microencapsulation technology in tissue engineering and protein delivery applications depends on the viability and functionality of the encapsulated cells, which in turn are dependent upon cell/matrix interactions. In this work, we compared the viability of cord blood-derived mesenchymal stromal cells (CB MSCs), engineered to secrete factor IX (FIX) for hemophilia treatment, and encapsulated in arginine-glycine-aspartate (RGD)-alginate versus fibrinogen-alginate microcapsules. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…With the increased focus on biomaterials engineered to support the growth of administered cells, a number of cell scaffolds and encapsulation approaches have been developed for specific niches and tissue types . MSCs are increasingly used in conjunction with these biomaterials, which are able to promote MSC differentiation to specific lineages.…”
Section: Discussionmentioning
confidence: 99%
“…With the increased focus on biomaterials engineered to support the growth of administered cells, a number of cell scaffolds and encapsulation approaches have been developed for specific niches and tissue types . MSCs are increasingly used in conjunction with these biomaterials, which are able to promote MSC differentiation to specific lineages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the viability of human mesenchymal stem cells (hMSCs) in alginate microcapsules is not optimal. We, and others, have decorated alginate with peptides or proteins that improve the cellular attachment of hMSCs on alginate (Yu et al, 2010; Sayyar et al, 2012, 2014, 2015). The addition of the amino acid residue RGD, fibrinogen or fibronectin enhanced cell viability, proliferation and/or transgene expression, as well as modulate stem cell differentiation.…”
Section: The Type Of Encapsulated Cells: Choice That Mattersmentioning
confidence: 99%
“…To address these obstacles, Hortelano et al have been investigating the ability of different biomaterials to improve cord blood-derived MSC viability and FIX production after transplantation. 28 They have shown that both arginine-glycine-aspartate (RGD) and fibrinogen-coated alginate-PLL microcapsules improve cell survival over noncoated microcapsules. However, only fibrinogen-coated microcapsules improved FIX secretion.…”
Section: Multipotent Adult Stem Cell Therapies: Mscsmentioning
confidence: 99%